The The Prevalence of Asymptomatic Bacteriuria among People Living in Public Compounds at Obinze Community of Imo State - E. Emeka Ikechukwu; E. Inya Joseph; J. Ofoegbu Chukwudi; E. Ogbonna Chinazom; H. Njoku Akudo; Chukwuemeka Njemanze Canice (International Journal of Public Health and Nursing, 2026)
The study was conducted between November 2024 and March 2025 using a well-structured questionnaire. Urine samples were collected after engaging Two Hundred (200) persons living in public compounds at Obinze, Imo State. The selected study group was given questionnaires to fill. The samples were collected with suitable sterile urine bottles and transported to the Microbiology Unit of Science Laboratory Technology Department FUTO, where they were processed and inoculated on cysteine lactose electrolyte-deficient media. The result showed that the mean age of the studied population was 32.9 years. The respondents aged 31–35 years were the highest, followed by those in the age range of 26–30 years. Most of the respondents did not receive formal education (68%), were mostly Christians (90%) whose average family size was 6.3 and married (80%). Ninety percent of the respondents have not heard about bacteriuria and did not know the bacterial load that constitutes them. There was a high level of knowledge about health practices and personal hygiene. They had high bacteria load in their urine because they were living in the public compounds. Respondents with normal urine samples ranged between 88% to 98%, but morphological and biochemical analyses showed a high percentage of Escherichia coli (56%), followed by Staphylococcus aureus (28%), Enterococcus spp. (6.7%), Pseudomonas aeruginosa (6.7%), and Klebsiella pneumoniae (2.6%). This indicated that the public compound inhabitants of Obinze may witness an outbreak of Urinary Tract Infection (UTI) at the nearest time. Personal hygiene and routine medical checks are necessary in the community.